PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PASIEN DI APOTEK RAHMA KRIAN SIDOARJO - Intan Kurnia Permatasari; Fadillah Tamammya Anshory (Politeknik Ubaya, 2023)
Marketing strategy is a way to achieve goals precisely by fulfilling the needs and desires of consumers through the exchange of goods or services. This study aims to determine the effect of the marketing mix with product, price, place, and promotion variables on patient satisfaction at Apotek Rahma. The type of research used is quantitative observation with a sample of 114 respondents and was conducted at the Rahma Krian Pharmacy Sidoarjo. The data collection technique uses a questionnaire that will be distributed to patients who will come to the pharmacy or who will consult a doctor. The analysis technique uses validity test, reliability test, multiple linear regression test, classical assumption test, and T test (partial), F test (simultaneous). The results showed that product and price variables had no effect on patient satisfaction, but place and promotion had an effect on patient satisfaction. Based on joint or simultaneous test, product, price, place, and promotion variables have a significant effect on patient satisfaction.